IMPLEMENTATION OF THE FAMILY PLANNING VILLAGE PROGRAM IN GAHARU VILLAGE, EAST MEDAN SUB-DISTRICT - Desi Trisnasari; Muhammad Arifin Nasution (Yayasan Wayan Marwan Pulungan, 2023)
The Family Planning Village (KB) program is one of the government's programs in the form of strategic innovation in implementing the priority activities of the Family Planning and Family Development (KKBPK) population program as a whole in the field. One of the implementations of the KB Village policy was carried out in the Gaharu Village, East Medan District. information about the community. This study aims to see how the implementation of the KB village program in the Gaharu sub-district, East Medan District. The research method used is descriptive research method with a qualitative approach. . The data obtained was then analyzed qualitatively by examining all the data that had been collected which was supported by the results of interviews with a theoretical approach according to Edward there were four variables in policy implementation namely; communication, Resources, Disposition and Bureaucratic Structure. From the research results it can be seen that there are still obstacles in process in implementing the KB Village Program. communication with the public is still relatively minimal. This resulted in the community not understanding the purpose of the KB Village program. The management has been provided with coaching and training, but there are still some managers who do not understand their duties and responsibilities. There is no commitment from the implementor to continue implementing the KB Village Program. The lack of management commitment to achieving common goals is also an obstacle in implementation.